Movement of Campus’ Mosque at UGM and UIN Sunan Kalijaga In Order to Understand National Politic - Flavius Florls Andrles (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
The emerging religious movement in campus areas after the reformation era is an interesting phenomenon to be researched. The aim of this study is to answer these questions: how to reconstruct the idea of religion and how the implementation of such idea in the religious movement to response the political problems. This research was conducted in two campuses with different background, Gadjah Mada University representing secular campus and Islamic state university Sunan Kalijaga representing religious campus. Findings of this research show that there is different religious understanding on the religious movement. In Gajah Mada mosque, the political problem is not discussed and is not included in the preaching. The reason is that the material is not relevant to mosque function. On the other hand, there is no problem to discuss about politics and also to say it in a preaching at the mosque in Islamic State University Sunan Kalijaga. This can happen because education about politics for people is part of mosque responsibility as a representation of muamalat in Islam.